Muslim Tourists' Purchase Intention Of Halal Food In Türkiye - Rusydiana, Aam Slamet; Maysyaroh, Siti; Awdalkrem, Hussein (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2024)
This study aims to explore the purchase intention of halal food products in Türkiye from the perspective of Muslim tourists. This study is a quantitative research using primary data. A total of 130 Muslims who have visited Türkiye became respondents and filled out this research questionnaire. The data obtained were then analyzed using the PLS-SEM method with the help of SmartPLS 3.0 software. The findings of this study indicate that halal credence and NFC (Need for Cognition) do not have a significant direct relationship with halal purchase intention. Both also have no significant indirect relationship with halal purchase intention through halal consumer attitudes as a mediating variable.